1997
DOI: 10.2307/3433366
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Neural Sensitization and Kindling Hypothesis for Illness from Low Levels of Environmental Chemicals

Abstract: 539-547 (1997)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Robinson and Becker (1986) concluded that behavioral sensitization or kindling is not unique to the psychopharmacology of stimulant drugs, but may be produced by many environmental stimuli that directly or indirectly activate brain catecholamine systems. A number of studies (Sorg et al, 1994;Bell et al, 1997a) have hypothesized that several human syndromes with poor medical diagnosis, including IEI and SBS, may involve chronic sensitization of catecholamine receptor systems resulting from repeated, low-level exposure to environmental chemical toxicants and stressors.…”
Section: Exposure Of Rats To Jp-4 Vapor 491mentioning
confidence: 98%
“…Robinson and Becker (1986) concluded that behavioral sensitization or kindling is not unique to the psychopharmacology of stimulant drugs, but may be produced by many environmental stimuli that directly or indirectly activate brain catecholamine systems. A number of studies (Sorg et al, 1994;Bell et al, 1997a) have hypothesized that several human syndromes with poor medical diagnosis, including IEI and SBS, may involve chronic sensitization of catecholamine receptor systems resulting from repeated, low-level exposure to environmental chemical toxicants and stressors.…”
Section: Exposure Of Rats To Jp-4 Vapor 491mentioning
confidence: 98%
“…It has been hypothesized (Bell et al, 1997a(Bell et al, , 1997b) that exposure to potent chemical odors may result in a "kindling-like" phenomenon by which inhaled chemicals can induce persisting changes in the excitabilit y of neuronal units in the olfactory bulbs and possibly in regions receiving secondary and tertiary inputs. The mechanism has been hypothesized as a possible basis for the development of such syndromes as IEI, through which a single high-dose exposure to an occupational or environmental chemical can ultimately result in widespread sensitivi ty to chemicals (foods, perfumes, ethanol, etc.)…”
Section: Olfactory Pathway Exposuresmentioning
confidence: 99%
“…There is mounting evidence that repeated exposure to low levels of certain volatile organic chemicals (VOCs), as are found as constituents of all hydrocarbon fuel formulations, may be involved in the etiology of such poorly defined diagnostic conditions as idiopathic environmental intolerance (IEI), chronic fatigue syndrome (CFS), sick building syndrome (SBS), tight building syndrome (TBS), fibromyalgia syndrome (FM), and Persian Gulf illnesses (PGI) (Bell et al, 1997a(Bell et al, , 1997bAshford & Miller, 1998). It is unknown whether repeated hydrocarbon fuel exposures, specifically those including exposure to low levels of multiple, potentially neurotoxic constituents, are sufficient to induce those syndromes commonly attributed to a single high-level exposure to one or more constituents.…”
mentioning
confidence: 99%
“…Sensitization is defined in the neuroscientific and pharmacologic literature as a progressive increase in the response to a set stimulus over time (3). Many traditional toxicologists and occupational health physicians argue that there is a lack of biological and toxicologic plausi-~ -bility for the notion that nontoxic levels of chemicals would result in symptoms characteristic of MCS.…”
mentioning
confidence: 99%